Пошаговое объяснение:
2x +4x-12=5x+5-9
6x-5x=12+5-9
x =8
1 шаг. Перепишем уравнение
2x+4(x-3)=5(x+1) -9
2 шаг. Раскроем скобки
2х+4х-12=5х+5-9
3 шаг. Упростим уравнение
6х-12=5х-4
4 шаг. Переведем иксы влево, числа вправо
6х-5х=-4+12
х=8
5 шаг. Проверка
2*8 + 4(8-3)=5(8+1)-9
16+20=45-9
36=36
ответ: х=8
Пошаговое объяснение:
2x +4x-12=5x+5-9
6x-5x=12+5-9
x =8
1 шаг. Перепишем уравнение
2x+4(x-3)=5(x+1) -9
2 шаг. Раскроем скобки
2х+4х-12=5х+5-9
3 шаг. Упростим уравнение
6х-12=5х-4
4 шаг. Переведем иксы влево, числа вправо
6х-5х=-4+12
х=8
5 шаг. Проверка
2*8 + 4(8-3)=5(8+1)-9
16+20=45-9
36=36
ответ: х=8